Estimation of Body Weight and Body Surface Area in Swamp Buffaloes using Visual Image Analysis - Buranakarl, Chollada; Indramangala, Jintana; Koobkaew, Kitti; Sanghuayphrai, Nikorn; Sanpote, Jureeratn; Tanprasert, Chularat; Phatrapornnant, Teera; Sukhumavasi, Woraporn; Nampimoon, Petcharat (Journal of Buffalo Science, 2012)
The three dimensional computerized visual image analysis was performed to evaluate the body weight (BW) and body surface area (BSA) in swamp buffaloes. Nineteen swamp buffaloes were measured the conformation by linear measurement compared to 3D body scanner at different points : body height (A), heart girth (B), shoulder width (C), iliac width (D), ischial tuberosity width (E), the length between shoulder and ileac wing (F, G), the length between ileal wing to ischial tuberosity (H, I) and the length between shoulder to ischial tuberosity (J1, J2). The significant correlation was found between these two methods. The 3D body scanner was then performed in 28 males and 39 females for BW and 68 males and 74 non-pregnant and 31 pregnant females for BSA estimation. The appropriate models to estimate BW in buffaloes were BW = - 1174.07 + 4.31 (B) + 7.75 (FG) (R2 = 0.76, P<0.001), BW (male) = -1265.99 + 4.94(B) + 14.41(D) (R2 = 0.81; P<0.001) and BW (female) = -563.66 + 7.94 (C) + 14.77 (E) (R2 = 0.86; P<0.001). For BSA, the appropriate equations were BSA = -4.31 + 0.034(A) + 0.036 (J1J2) (R2 = 0.82, P<0.001), BSA (male) = -4.01 + 0.032 (A) + 0.037 (J1J2) (R2 = 0.816, P<0.001) and BSA (female) = -3.50 + 0.013(A) + 0.012 (B) + 0.040 (E) + 0.015 (J1J2) (R2 = 0.916, P<0.001). In conclusion, the 3D body scanner can be used to estimate BW and BSA in buffaloes with different models among males and females.